Transient GUS assay based quick screening method of genes cloned in a binary vector in tandem for plant transformation - Khomdram, Shusma; Barthakur, Sharmistha (Annals of Agricultural Research, 2016)
The Escherichia coli Î²-glucuronidase gene (GUS) was used as a gene stacking marker for analysisof genes to be mobilized and expressed in transformed plants. Higher plants lack intrinsicÎ²-glucuronidase activity, thus enhancing the sensitivity with which measurements can be made.A gene stacking cassette was constructed in binary vector pBi121 under the control of cauliflowermosaic virus (CaMV) 35S promoter along with a gene encoding transcription factor from wheatWRKY10 before the GUS reporter gene to direct the expression of both the genes in transformedplants through Agrobacterium mediated transformation. After PCR confirmation of cloning,expression of GUS was done which could be observed both in bacterial culture suspension andtransiently expressed in explants of Nicotiania tabacum. This quick initial screening using GUS canbe performed for cloning more than one gene for further downstream applications. The resultsconfirmed expression of both the genes in tandem in Agrobacterium as well as in plant system andcan be used to stack stably more than two genes for manipulating important plant growth anddevelopmental traits.